2021
DOI: 10.1002/jez.b.23104
|View full text |Cite
|
Sign up to set email alerts
|

Macrowear effects of external quartz abrasives of different size and concentration in rabbits (Oryctolagus cuniculus)

Abstract: External quartz abrasives are one of the driving forces of macrowear in herbivorous animals. We tested to what extent different sizes and concentrations influence their effect on tooth wear. We fed seven pelleted diets varying only in quartz concentration (0%, 4%, and 8%) and size (fine silt: 4 m, coarse silt: 50 m, fine sand: 130 m) to rabbits (Oryctolagus cuniculus, n = 16) for 2 weeks each in a randomized serial experiment. Measurements to quantify wear and growth of incisors and the mandibular first cheek … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
(112 reference statements)
0
8
0
Order By: Relevance
“…Additionally, when the fine silt and the fine sand were compared directly in feeding experiments in vivo , no difference in macroscopic tooth wear between these abrasives was detected [ 19 , 21 ]. In terms of microwear texture, the fine silt leads to a pattern of ‘enamel polishing’ with smoother surfaces compared to controls, whereas the fine sand leads to a pattern of ‘enamel scratching’ with rougher surfaces compared to controls [ 34 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, when the fine silt and the fine sand were compared directly in feeding experiments in vivo , no difference in macroscopic tooth wear between these abrasives was detected [ 19 , 21 ]. In terms of microwear texture, the fine silt leads to a pattern of ‘enamel polishing’ with smoother surfaces compared to controls, whereas the fine sand leads to a pattern of ‘enamel scratching’ with rougher surfaces compared to controls [ 34 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to dental wear, one of the impressive functional differences is the rate of tissue loss in ever-growing (hypselodont or euhypsodont) teeth as compared to non-ever-growing teeth. In hypselodont teeth (both incisors and cheek teeth), wear rates of a magnitude of several millimetres per week are known [ 13 19 ], with a corresponding, compensating growth rate. By contrast, mammalian herbivores with non-ever-growing teeth yet similar diets show cheek tooth wear rates at a magnitude of millimetres per year [ 13 , 20 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The experiments are here designated as A–C, with a subscript denoting the species (A r –C r for rabbits, C gp for guinea pigs). Details on the husbandry, diets and tooth wear have been previously published: Experiment A r was designed to test the effect of diet consistency on tooth wear in rabbits (Martin, Ackermans, Tollefson, et al, 2021 ); experiment B r to test the effect of additions of different concentrations and sizes of quartz silica on tooth wear in rabbits (Martin, Ackermans, Richter, et al, 2021 ); experiment C to test effects of different levels of phytoliths and the addition of sand on tooth wear in rabbits (Cr; Müller et al, 2014 ) and guinea pigs (Cgp; Müller et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…We used computed tomography (CT) images to test our prediction on differences in sand accumulation in the GIT of rabbits and guinea pigs. CT scans of heads and teeth had been generated in several studies evaluating the effect of different siliceous abrasives on tooth wear in rabbits and guinea pigs (Martin, Ackermans, Richter, et al, 2021 ; Martin, Ackermans, Tollefson, et al, 2021 ; Müller et al, 2014 ; Müller et al, 2015 ). In those same experiments, CT scans of the abdomen had also been acquired to document the deposition of the radiopaque abrasives in the GIT.…”
Section: Introductionmentioning
confidence: 99%
“…This includes studies of neglected but important organ systems such as the inner ear (Evin et al, 2022), and of developmental plasticity as expressed in osteological variation resulting from husbandry (Neaux et al, 2022). Moreover, our understanding of tooth development and evolution can also benefit from experimental studies that reveal unsuspected plasticity of growth in dental tissues in response to different diets (Martin et al, 2022). The study of tooth proportions in an extensive sample of horses and cattle showed the relevance of allometric effects and differential evolvability of craniodental modules to understand unoccupied morphospace in some domesticates (Clauss et al, 2022).…”
mentioning
confidence: 99%